A Life-Cycle Model of Outmigration and Economic Assimilation of Immigrants in Germany - Charles Bellemare (Institute for the Study of Labor (IZA), 2004)
This paper estimates a structural dynamic life-cycle model of outmigration where, in each period, immigrants choose whether to work in the host country, not to work but remain in the host country, or outmigrate. The model incorporates several features of existing life-cycle theories of outmigration but distinguishes itself by introducing uncertainty in about future earnings and preferences which allows immigrants to revise their duration decisions throughout their migration experience. We overcome the problem of not directly observing outmigration movements by using panel attrition as a proxy variable and use a simple method to correct for the fact that part of the attrition is not a consequence of outmigration. Estimates are used to predict changes in life-cycle patterns of outmigration behavior. Estimation results indicate that outmigration does not depend exclusively on earnings differentials. Estimated assimilation rates are found to be robust to selection effects. Immigrants are found to be forward looking decision makers, and simulations show that predicted migration durations are very sensitive to changes in their economic environment and differ considerably from those of a myopic model.
Keywords: J61; C61; 330; outmigration; structural dynamic programming models; Rückwanderung; Einwanderung; Soziale Integration; Migrationstheorie; Dynamische Optimierung; Lebenszyklus; Schätzung; Deutschland